QM/MM computations reveal details of the acetyl-CoA synthase catalytic center - Elghobashi-Meinhardt, Nadia; Tombolelli, Daria; Mroginski, Maria-Andrea (Biochimica et biophysica acta. General subjects, 2020)
The “open” (Aopen) and “closed” (Aclosed) A-clusters of the acteyl-CoA synthase (ACS) enzyme from Moorella thermoacetica have been studied using a combined quantum mechanical (QM)/molecular mechanical (MM) approach. Geometry optimizations of the oxidized, one- and two-electron reduced Aopen state have been carried out for the fully solvated ACS enzyme, and the CO ligand has been modeled in the reduced models. Using a combination of both αopen and αclosed protein scaffolds and the positions of metal atoms in these structures, we have been able to piece together critical parts of the catalytic cycle of ACS. We have replaced the unidentified exogenous ligand in the crystal structure with CO using both a square planar and tetrahedral proximal Ni atom. A one-electron reduced A-cluster that is characterized by a proximal Ni atom in a tetrahedral coordination pattern observed in both the Aopen (lower occupancy proximal Ni) and Aclosed (proximal Zn atom) geometries with three cysteine thiolates and a modeled CO ligand demonstrates excellent agreement with the crystal structure atomic positions, particularly with the displacement of the side chain ring of Phe512 which appears to serve as a structural gate for ligand binding. The QM/MM optimized geometry of the A-cluster of ACS with an uncoordinated, oxidized proximal nickel atom in a square planar geometry demonstrates poor agreement with the atomic coordinates taken from the crystal structure. Based on these calculations, we conclude that the square planar proximal nickel coordination that has been captured in the Aopen structure does not correspond to the ligand-free, oxidized [Fe4S4]2+ − Nip2+ − Nid2+ state. Overall, these computations shed further light on the mechanistic details of protein conformational changes and electronic transitions involved in the ACS catalytic cycle. •QM/MM computations reveal atomic details of Aopen and Aclosed catalytic centers in acetyl-CoA synthase (ACS)•Geometry of one-electron reduced A-cluster with CO ligand and tetrahedral proximal Ni atom agrees with the crystal structure•Rotation of the side chain ring of Phe512 appears to serve as a structural gate for ligand binding•Aopen with square planar proximal nickel does not correspond to the ligand-free, oxidized [Fe4S4]2+--Nip2+--Nid2+ state